The Role of Moral Emotions in Military Trauma: Implications for the Study and Treatment of Moral Injury. Issue 4 (December 2014) - Farnsworth, Jacob K.; Drescher, Kent D.; Nieuwsma, Jason A.; Walser, Robyn B.; Currier, Joseph M.
Moral injury, a term coined to represent the potential negative outcomes following transgression of deeply held moral values and beliefs, has recently gained increased recognition as a major concern among military service members exposed to trauma. However, working definitions of moral injury have not yet fully clarified the mechanisms whereby violations of conscience result in these outcomes or their co-occurrence with posttraumatic stress disorder (PTSD). In this paper, advances from the field of moral psychology are used to integrate cognitive, affective, and social dimensions of the emerging moral injury construct, while also pointing to new possibilities for clinical intervention. After reviewing the salience of moral injury for military and veteran populations, the presence of negative moral emotions (e.g., guilt, anger, disgust) are examined within the context of trauma and military-related PTSD. Next, social functionalist accounts of moral emotions are used to explain the development of moral injury and are linked to potential etiologies of PTSD that emphasize both fear and nonfear emotions. Finally, the clinical importance of positive moral emotions for existing and emerging trauma-focused interventions is discussed. Future directions for research and clinical interventions are identified highlighting the importance of utilizing community support.